Cancer susceptibility of beta HPV49 E6 and E7 transgenic mice to 4-nitroquinoline 1-oxide treatment correlates with mutational signatures of tobacco exposure - Viarisio, Daniele; Robitaille, Alexis; Müller-Decker, Karin; Flechtenmacher, Christa; Gissmann, Lutz; Tommasino, Massimo (Virology, 2019)
We have previously showed that a transgenic (Tg) mouse model with cytokeratin 14 promoter (K14)-driven expression of E6 and E7 from beta-3 HPV49 in the basal layer of the epidermis and of the mucosal epithelia of the digestive tract (K14 HPV49 E6/E7 Tg mice) are highly susceptible to upper digestive tract carcinogenesis upon exposure to 4-nitroquinoline 1-oxide (4NQO). Using whole-exome sequencing, we show that in K14 HPV49 E6/E7 Tg mice, development of 4NQO-induced cancers tightly correlates with the accumulation of somatic mutations in cancer-related genes. The mutational signature in 4NQO-treated mice was similar to the signature observed in humans exposed to tobacco smoking and tobacco chewing. Similar results were obtained with K14 Tg animals expressing mucosal high-risk HPV16 E6 and E7 oncogenes. Thus, beta-3 HPV49 share some functional similarities with HPV16 in Tg animals.
Gesehen am 20.04.2020